Discapacidad intelectual y su incidencia en el aprendizaje de un joven de 15 años de la Parroquia San Juan - Veintimilla Solórzano, Isai Natanael (2023)
The present work carried out is a case study on intellectual disability and its impact on learning, so that necessary information is obtained for the understanding of intellectual disability and their personal development process, by understanding each of them as individuals with cognitive abilities that are related to reasoning and obtaining skills. It is important to know that through a psycho-pedagogical process it will be possible to determine the repercussions of intellectual disability in the academic area, which will allow an approach from a multidisciplinary perspective, with detailed information as it observes the following study and therefore promote answers to this problem. It is worth mentioning that the research consists of a theoretical support, where verified information is compiled from different authors; applied techniques such as observation, interview, test with their respective instruments; methodology that covers from a qualitative, descriptive and analytical approach; obtained results and its conclusion, in effect, will be fundamental to apply in practice within the adaptive processes.